Psychological States and their Relationship to Mental Health from an Islamic Point of View - Alazzam, Abdul Nasser; Alzoubi, Mohammad (Dirasat: Educational Sciences, 2021)
The study aims to identify the states of the self and their relationship to mental health from an Islamic point of view. Original, analytical and deductive approaches were used. The study concluded that the soul has three main states: the self that commands bad behavior, the self that is disorganized, and the self that is reassuring. These states have a direct relationship to mental health. The bad self represents a deviation from the normal level of mental health because it appeals to the physical side at the expense of the spiritual side. The disordered self represents a deviation from the normal level of mental health because it appeals to the spiritual side at the expense of the physical side. The reassuring self represents the basis of mental health because it balances the requirements of the body and spirit. The study recommends conducting more studies related to mental health in Islam.